Use of extended criteria of donors in liver transplantation - Miranda, Luiz Eduardo Correia; Macedo, Francisco Igor Bulcão de; Fonseca Neto, Olival Cirilo Lucena; Lacerda, Cláudio Moura (Brazilian Journal of Transplantation, 2007)
The use of marginal/extended criteria for organ donors is a solution to the problem of organ donors shortage, and since its use has become more common worldwide, concerns on the effectiveness of such organs and the outcomes of the liver transplantation (LT) have been raised. In spite of the importance of the term, there is no consensus on the features of the marginal donors. Some parameters related to the features of those donors were found to have negative consequences: increasing donor or recipient age, longer cold ischemia time, hypotension and inotropic support, gender mismatch, after cardiac death donation, hearts that stopped beating, non-heart-beating donors, and macrosteatosis. This paper discusses some controversial issues found in the literature, and shares our experience related to the use of marginal/extended criteria of donor in liver transplantation.